Penerapan PIECES Framework dalam Analisis Kepuasan Pengguna F-Learn UKSW saat Pandemi Covid-19 - Eric Bintang Pangentasan; Evi Maria (Jurnal Sistem Informasi Bisnis, 2023)
This research aimed to analyze the satisfaction level of Satya Wacana Christian University (SWCU) F-Learn users in daring learning during the Covid-19 pandemic using the PIECES framework. This method was chosen because it has proven its effectiveness in evaluating system user satisfaction in identifying problems, opportunities and development directions for the system being developed. This research analyzes six variables: performance, information and data, economics, control and security, efficiency, and service. The research sample for this was SWCU students. The total sample is 160 respondents. Data was measured using a Likert scale. The results of testing on the variables performance, information and data, control and security, efficiency, and service, users feel satisfied, while testing the economics variables, F-Learn users feel very satisfied. Additional testing on the performance of F-Learn confirmed that F-Learn has an excellent performance in terms of the speed of responding to commands, as well as in terms of control F-Learn is in category B (good). Overall, the average level of satisfaction of F-Learn users is 4.02. It means that overall F-Learn users, namely SWCU students, were satisfied when using F-Learn during the implementation of the daring learning policy during the pandemic.